4-(3-Methoxyphenyl)-2,6-dimethylcyclohex-3-enecarboxylic acid - Xie, Songwen (International Union of Crystallography, 2010)
The racemic title compound, C(16)H(20)O(3), was synthesized to study the hydrogen-bonding interaction of the two enantiomers in the solid state. In the crystal structure, R and S pairs of the racemate are linked by pairs of intermolecular O—H⋯O hydrogen bonds, producing centrosymmetric R (2) (2)(8) rings.